Brothers of the gun : a memoir of the Syrian War - Hisham, Marwan; Crabapple, Molly (New York : One World, 2018)
A journalist who came of age on the frontlines of the Syrian War provides a new perspective into the deadly conflict and reveals how profound acts of courage, creativity, and hope can be found, even in the darkest places.
Keywords: Hisham, Marwan; Hisham, Marwan; Journalists -- Syria -- Biography; Terrorism -- History -- Syria -- 21st century; Journalists -- Syria -- Biography; Terrorism -- Syria -- History; Syria -- History -- Civil War, 2011- -- Biography; Syria -- History -- 21st century -- Biography; Biographies